One year at Ellsmere - Hicks, Faith Erin (First Second, 2020)
When Juniper arrives at the Ellsmere girls' boarding school by means of a scholarship, she soon finds that many of the privileged rich girls see "scholarship student" as a code for charity case. Fortunately, Juniper finds a friend in Cassie, who tells her legends of a beautiful creature that lives in the forest outside of the school.